Evaluation of the empathic skills of nursing students with respect to the classes they are attending - Nursan Çınar; Reyhan Cevahir; Sevil Şahin; Cefariye Sözeri; Sema Kuğuoğlu (Universidade Federal de Goias, 2007)
The study was carried out, as a descriptive and comparative one, with the aim of evaluating the empathic skills of the students of the Nursing Department of Sakarya University School of Health Sciences. The universe of the study comprised 139 students . The sampling comprised 104 students who had been able to take part in the study. As the means of data collecting, a 22-question survey form and the 'Empathic Skill Scale B-Form' which Dökmen (1988) had put into application by testing the validity and reliability for our country. In the evaluation, percentage, Students 't' Test, Mann-Whitney U Test were employed.The average of the empathic skill points of the students included in the study was found to be 139.45 ± 20.47. According to the results of our study, scores of empathic skill of Grade I students are higher comparing to Grade II and III students. This case may depend on the fact that the communication lessons are more intensive in this grade. Again, increasing of empathic skill points in Grade IV made us think that the application opportunities of psychiatric nursing lessons taken in this grade had been effective on the development of empathic skills of students.